OCT-4 Is a Good Predictive Biomarker for Local Recurrence in Head and Neck Basal Cell Carcinoma - Fereshteh Baghai Naini; Kambiz Kamyab Hesari; Nazanin Mahdavi; Samira Derakhshan (Islamic Dental Association of Iran, 2017)
Background and Aim: Basal cell carcinoma (BCC) is considered to be the most common malignancy in humans and occurs primarily in the skin especially in the head and neck region. Considering the high recurrence rate of the tumor, finding a marker for prediction of recurrence is very important. Cancer stem cells are a small subpopulation in the tumors that are related to tumorigenesis and recurrence and OCT4 is a known stem cell marker. The present study was designed to explore the relation between expres-sion of OCT4 in the head and neck basal cell carcinoma and recurrence of the tumor. Materials and Methods: This study was performed on 84 patients with head and neck BCC who were followed up for 24 months. Immunohistochemical expression of OCT4 was assessed in paraffin embedded blocks. Results: Positive expression of OCT4 was significantly associated with the recurrence rate (P<0.001). Conclusion: We conclude that the expression of OCT4 can serve as a predictive marker for tumor recurrence in the head and neck basal cell carcinoma.